2021
DOI: 10.1002/etc.5131
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Delayed Mortality of Ceriodaphnia dubia and Rainbow Trout Following Time‐Varying Acute Exposures to Zinc

Abstract: The potential for delayed mortality following short-term episodic pollution events was evaluated by exposing cladocerans (Ceriodaphnia dubia) and rainbow trout (Oncorhynchus mykiss) to zinc (Zn) in various 1-to 48-h and 1-to 96-h exposures, respectively, followed by transferring the exposed organisms to clean water for up to 47 h for C. dubia and up to 95 h for trout for additional observation. For C. dubia, 1-h exposures of up to 3790 µg Zn/L never resulted in mortality during the actual Zn exposures, but by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Latent effects of metals to aquatic organisms have been reported in previous pulsed exposure studies (Angel et al, 2010;Brent & Herricks, 1998;Bucher et al, 2006;Colvin et al, 2021;Hoang, Gallagher, Tomasso et al, 2007;Hoang & Klaine, 2008;Mebane et al, 2021;Zahner et al, 2006;Zhao & Newman, 2006). After a pulsed exposure ends, it is highly suggested that heavy metals continue to exert their toxic effects post-exposure, which is exemplified by the observation of latent effects.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Latent effects of metals to aquatic organisms have been reported in previous pulsed exposure studies (Angel et al, 2010;Brent & Herricks, 1998;Bucher et al, 2006;Colvin et al, 2021;Hoang, Gallagher, Tomasso et al, 2007;Hoang & Klaine, 2008;Mebane et al, 2021;Zahner et al, 2006;Zhao & Newman, 2006). After a pulsed exposure ends, it is highly suggested that heavy metals continue to exert their toxic effects post-exposure, which is exemplified by the observation of latent effects.…”
Section: Discussionmentioning
confidence: 91%
“…Brent and Herricks (1998) also found greater proportions of the total mortality of both organisms after exposures ended for Zn than for Cd. Mebane et al (2021), however, studied Zn only and found strong latent effects of Zn on the mortality of <24‐h‐old C. dubia at an exposure time of <24 h and at Zn concentrations of µg/L. In general, lower treatment concentrations required a longer period before total cumulative mortality was achieved, suggesting that lower metal concentrations might take longer to exert visible latent effects as metals need to enter and accumulate in the organism to a level that exceeds the organism's tolerance to exert effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). In general, during post-exposure periods, animals exposed to metals show an increase of mortality (Pascoe and Shazili 1986 ; Handy 1994 ; Schill et al 2003 ; Zhao and Newman 2004 , 2006 ; Hoang et al 2007 ; Mebane et al 2021 ). In our study this was especially marked in the highest concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, the true mechanisms of toxicity may be known, even for well‐studied substances and organisms, such as the chronic toxicity of metals to fish (Wood, 2012). Complicating this surrogacy in exposures are lag times between exposure and effects (Diamond et al, 2006; Mebane et al, 2021). In some case studies with organic chemicals, these depuration and recovery times were in the range of 5–30 days (Landrum et al, 2004; Landrum et al, 2013).…”
Section: Approachmentioning
confidence: 99%